The aquaporin-3-inhibiting potential of polyoxotungstates - Pimpão, Catarina (2020)
Polyoxometalates (POMs) are of increasing interest due to their proven anticancer activities. Aquaporins (AQPs) were found to be overexpressed in tumors bringing particular attention to their inhibitors as anticancer drugs. Herein, we report for the first time the ability of polyoxotungstates (POTs), such as of Wells-Dawson P2W18, P2W12, and P2W15, and Preyssler P5W30 structures, to affect aquaporin-3 (AQP3) activity and impair melanoma cell migration. The tested POTs were revealed to inhibit AQP3 function with different effects, with P2W18, P2W12, and P5W30 being the most potent (50% inhibitory concentration (IC50) = 0.8, 2.8, and 3.2 µM), and P2W15 being the weakest (IC50 > 100 µM). The selectivity of P2W18 toward AQP3 was confirmed in yeast cells transformed with human aquaglyceroporins. The effect of P2W12 and P2W18 on melanoma cells that highly express AQP3 revealed an impairment of cell migration between 55% and 65% after 24 h, indicating that the anticancer properties of these compounds may in part be due to the blockage of AQP3-mediated permeability. Altogether, our data revealed that P2W18 strongly affects AQP3 activity and cancer cell growth, unveiling its potential as an anticancer drug against tumors where AQP3 is highly expressed.